THE ROLE OF COMMUNALISM IN INDIAN POLITICS –AN OVERVIEW - Vanaja (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Communalism is an extremely complex phenomenon. It is generally associated with plural societies. While in the West, communalism alludes to the feelings and a concern for the community and is used in a positive sense in India the term ‘communalism’ has a negative connotation; it is used to designate the process of mobilizing a community to confront another community. More specifically communalism is regarded as a manifestation of confrontation between the minority community and the majority community. India, the multicultural and religious nation has also a very special political feature, the different caste and communal elements determining the stability and instability of the Indian politics. In India, no coalition ministry can come in to political power without the support of caste and communal groups, the caste ridden politics in India, in the context of secular state is also analyzed in this study. Here, the researcher uses the term ‘communalism’ to denote the major religion based or community based political parties and how it influences the stability and instability of the power politics of India.